Differential Roles for Cyclin-Dependent Kinase Inhibitors p21 and p16 in the Mechanisms of Senescence and Differentiation in Human Fibroblasts - Stein, Gretchen H. (American Society for Microbiology, 1999)
The irreversible G(1) arrest in senescent human diploid fibroblasts is probably caused by inactivation of the G(1) cyclin–cyclin-dependent kinase (Cdk) complexes responsible for phosphorylation of the retinoblastoma protein (pRb). We show that the Cdk inhibitor p21(Sdi1,Cip1,Waf1), which accumulates progressively in aging cells, binds to and inactivates all cyclin E-Cdk2 complexes in senescent cells, whereas in young cells only p21-free Cdk2 complexes are active. Furthermore, the senescent-cell-cycle arrest occurs prior to the accumulation of the Cdk4-Cdk6 inhibitor p16(Ink4a), suggesting that p21 may be sufficient for this event. Accordingly, cyclin D1-associated phosphorylation of pRb at Ser-780 is lacking even in newly senescent fibroblasts that have a low amount of p16. Instead, the cyclin D1-Cdk4 and cyclin D1-Cdk6 complexes in these cells are associated with an increased amount of p21, suggesting that p21 may be responsible for inactivation of both cyclin E- and cyclin D1-associated kinase activity at the early stage of senescence. Moreover, even in the late stage of senescence when p16 is high, cyclin D1-Cdk4 complexes are persistent, albeit reduced by ≤50% compared to young cells. We also provide new evidence that p21 may play a role in inactivation of the DNA replication factor proliferating cell nuclear antigen during early senescence. Finally, because p16 accumulates in parallel with the increases in senescence-associated β-Gal activity and cell volume that characterize the senescent phenotype, we suggest that p16 upregulation may be part of a differentiation program that is turned on in senescent cells. Since p21 decreases after senescence is achieved, this upregulation of p16 may be essential for maintenance of the senescent-cell-cycle arrest.